Prevention and reversal of obesity and glucose intolerance in mice by DHA derivatives - Rossmeisl, Martin; Jelenik, Tomas; Jilkova, Zuzana; Slamova, Kristyna; Kus, Vladimir; Hensler, Michal; Medrikova, Dasa; Povysil, Ctibor; Flachs, Pavel; Mohamed-Ali, Vidya; Bryhn, Morten; Berge, Kjetil; et al. (Obesity (Silver Spring, Md.), 2009)
The n-3 polyunsaturated fatty acids, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), exert hypolipidemic effects and prevent development of obesity and insulin resistance in animals fed high-fat diets. We sought to determine the efficacy of alpha-substituted DHA derivatives as lipid-lowering, antiobesity, and antidiabetic agents. C57BL/6 mice were given a corn oil-based high-fat (35% weight/weight) diet (cHF), or cHF with 1.5% of lipids replaced with alpha-methyl DHA ethyl ester (Substance 1), alpha-ethyl DHA ethyl ester (Substance 2), alpha,alpha-di-methyl DHA ethyl ester (Substance 3), or alpha-thioethyl DHA ethyl ester (Substance 4) for 4 months. Plasma markers of glucose and lipid metabolism, glucose tolerance, morphology, tissue lipid content, and gene regulation were characterized. The cHF induced obesity, hyperlipidemia, impairment of glucose homeostasis, and adipose tissue inflammation. Except for Substance 3, all other substances prevented weight gain and Substance 2 exerted the strongest effect (63% of cHF-controls). Glucose intolerance was significantly prevented (~67% of cHF) by both Substance 1 and Substance 2. Moreover, Substance 2 lowered fasting glycemia, plasma insulin, triacylglycerols, and nonesterified fatty acids (73, 9, 47, and 81% of cHF-controls, respectively). Substance 2 reduced accumulation of lipids in liver and skeletal muscle, as well as adipose tissue inflammation associated with obesity. Substance 2 also induced weight loss in dietary obese mice. In contrast to DHA administered either alone or as a component of the EPA/DHA concentrate (replacing 15% of dietary lipids), Substance 2 also reversed established glucose intolerance in obese mice. Thus, Substance 2 represents a novel compound with a promising potential in the treatment of obesity and associated metabolic disturbances.
Keywords: Male; hmotnostní přírůstek; glukózový toleranční test; polymerázová řetězová reakce; triglyceridy; kyseliny dokosahexaenové; Polymerase Chain Reaction; Glucose Tolerance Test; Mice, Inbred C57BL; Animals; porucha glukózové tolerance; Glucose; Hypolipidemic Agents; Mice; myši inbrední C57BL; obezita; Energy Intake; Obesity; mužské pohlaví; RNA; glukosa; dietní tuky; modely nemocí na zvířatech; Glucose Intolerance; Weight Gain; hypolipidemika; zvířata; Docosahexaenoic Acids; energetický příjem; Dietary Fats; Triglycerides; Disease Models, Animal; myši